2018
DOI: 10.3390/polym10070805
|View full text |Cite
|
Sign up to set email alerts
|

Coupling of Defect Modes in Cholesteric Liquid Crystals Separated by Isotropic Polymeric Layers

Abstract: Abstract:Cholesteric liquid crystal structures with multiple isotropic defect layers exhibit localized optical modes (defect modes). Coupling effects between these modes were simulated using the finite difference time domain method. Analogous to the well-known result of the tight-binding approximation in solid state physics, splitting of the defect modes takes place, as soon as the structure contains more than one defect layer. The dispersion relation of the mini-bands forming within the photonic band gap of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 37 publications
2
11
0
Order By: Relevance
“…Figure 2d reveals a dominant right circular polarization (RCP) component with a small amount of left circular polarization light. For an isotropic defect layer, which is the configuration used here, previous research has shown that the polarization of the mode is typically observed to be circularly polarized of the same handedness as that of the CLC helix 34–36. Our results are in broad agreement in that we see a dominant RCP component in accordance with the right‐handed helix of our CLC layers.…”
Section: Figuresupporting
confidence: 86%
“…Figure 2d reveals a dominant right circular polarization (RCP) component with a small amount of left circular polarization light. For an isotropic defect layer, which is the configuration used here, previous research has shown that the polarization of the mode is typically observed to be circularly polarized of the same handedness as that of the CLC helix 34–36. Our results are in broad agreement in that we see a dominant RCP component in accordance with the right‐handed helix of our CLC layers.…”
Section: Figuresupporting
confidence: 86%
“…Here we employ such unique properties of CLCs to realize tunable topological lasers at low cost. We analyze the coupling of defect modes in the P-CLC superlattices and demonstrate that the mini-bands can be designed in the bandgap of the CLC, which has been proposed to achieve visible defect mode lasing with a low threshold [57]. In experiments, we apply an out-of-plane liquid crystal orientation technology based on the femtosecond laser direct writing (FLDW) method recently developed by our group [58].…”
Section: Resultsmentioning
confidence: 99%
“…As shown in Fig 1(a, b1), the distances between the weakly and strongly coupled ribbons are chosen to be d 1 = 34×(p/2) and d 2 = 22×(p/2), respectively. The width of each polymer ribbon is set to be d i = 2 μm, which is thick enough to give rise to two defect modes in the bandgap of the CLC [57]. The two P-CLC SSH superlattices in either side of the interface have the same mini-band structure, but they possess different topological properties that are characterized by their winding numbers [60][61][62][63].…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, these materials self-organize their periodic structure and form a photonic bandgap (PBG) where circularly polarized light with the same handedness as that of the CLC helix cannot propagate [ 6 ]. Several studies on chiral photonic crystals have shown that it is possible to create localized optical modes within the PBG by inducing a defect into the periodic structure [ 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%